Comparative Effectiveness of Mineral Trioxide Aggregate (MTA) and Calcium Hydroxide in Partial Biopulpectomies of Mus musculus teeth (Revista de Ciências Agroveterinárias, 2025)
This study compared the effectiveness of Calcium Hydroxide and Mineral Trioxide Aggregate (MTA) in partial biopulpectomies of Mus musculus teeth. A total of 16 rats (n=8 per group) were used, evaluating inflammation (levels 1: very mild to 4: severe), necrosis, and granulation tissue formation at 7 and 21 days. Using non-parametric tests (Fisher’s exact test, McNemar, Wilcoxon, and Mann-Whitney), no significant intergroup differences were found in inflammation (p > 0.05 at 7 days; p > 0.05 at 21 days) or necrosis (p > 0.05 at 7 days; p > 0.05 at 21 days). However, MTA exhibited superior clinical trends, achieving complete necrosis resolution (0% vs. 25% in Calcium Hydroxide) and granulation tissue formation (100% vs. 87.5%) at 21 days, with significant intragroup reductions in granulation (p < 0.05 vs. p < 0.05). The wide confidence intervals (e.g., necrosis in MTA at 21 days: 0.0–36.9%) and moderate effect sizes (φ=0.42; r=-0.45) reflected sample size limitations, highlighting the need for larger studies. While both materials demonstrated biocompatibility, MTA emerges as a preferred option in contexts prioritizing comprehensive tissue repair, supported by its profile without post-operative complications. These findings provide preliminary evidence to guide future multidisciplinary investigations with greater statistical power.
Keywords: inflammatory cellular response; presence of necrosis areas; granulation tissue formation; therapeutic dentistry